La fabrique des sports nationaux. A History of the Swiss sporting elite (late 19th-early 20th century) - Grégory Quin; Philippe Vonnard; Gil Mayencourt; Sébastien Cala (Bern Open Publishing, 2023)
The present contribution presents the results of the eponymous research project, which focuses on the understanding of the genesis and structure of the Swiss sports field between the 1860s and the 1930s. During this period, national umbrella organisations for all physical activities and sports developed. Within the framework of this project, which focuses on several sports (gymnastics, shooting, national games, football and cycling, with the addition of skiing on the basis of related doctoral work), we will present our main results, in particular on the organisations in charge of the governance of the sports identified as central, in order to shed light on the struggles but also on the links that were to be forged between them, as well as to question the recruitment, the profiles and the motivations of their leading elites. Based on the collection and analysis of unpublished documentation, especially prosopographical, this project brings to light a double original process to which the space of physical and sports activities is subjected: on the one hand, that of sportivisation, on the other hand, that of nationalisation. In the framework of this contribution, we will present a selection of emblematic cases of presidents of Swiss sports federations, at the time of the Fin-de-Siècle and up to the interwar period, o compare the different traditions existing in the studied sports and to underline the processes leading to the status of "national sports".